2015
DOI: 10.1016/j.ajpath.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Il10 Alleviates the Systemic Antiviral Cellular Immune Response and T Cell–Mediated Immunopathology in Select Organs of Acutely LCMV-Infected Mice

Abstract: The immunoregulatory cytokine IL-10 suppresses T-cell immunity. The complementary question, whether IL-10 is also involved in limiting the collateral damage of vigorous T cell responses, has not been addressed in detail. Here, we report that the particularly strong virus-specific immune response during acute primary infection with the lymphocytic choriomeningitis virus (LCMV) in mice is significantly further increased in Il10-deficient mice, particularly regarding frequencies and cytotoxic activity of CD8(+) T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Consistent with this, IL-10 is important for limiting the detrimental effects of inflammatory cytokines and subsequent pathology during infection (Jakobshagen et al 2015;Claser et al 2017), and polymorphisms in IL-10 leading to lower IL-10 expression are associated with increased susceptibility to sepsis (Gallagher et al 2003;Schaaf et al 2003). These findings, along with the data presented here, suggest that the anti-IL-10R1 mAb could enhance inflammatory responses in disease settings where IL-10 actively suppresses the responses.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with this, IL-10 is important for limiting the detrimental effects of inflammatory cytokines and subsequent pathology during infection (Jakobshagen et al 2015;Claser et al 2017), and polymorphisms in IL-10 leading to lower IL-10 expression are associated with increased susceptibility to sepsis (Gallagher et al 2003;Schaaf et al 2003). These findings, along with the data presented here, suggest that the anti-IL-10R1 mAb could enhance inflammatory responses in disease settings where IL-10 actively suppresses the responses.…”
Section: Discussionsupporting
confidence: 86%
“…However, it is not clear whether the induction of gingival IL-10 expression in ligature-induced experimental periodontitis was mainly or partly from B10 activation in the gingival tissue under the combination treatment. Recent studies indicated that IL-10 was secreted not only form B cell s but also from other types of immune cells such as regulator T cells [35,36], dendritic cells [37,38], macrophages [39,40]. Thus, the increase of gingival IL-10 expression may be caused by stimulation on other type of cells as well, suggesting further studies are needed for IL-21, anti-Tim1 and CD40L combination effects on other types of immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many negative immune regulators have been discovered and/or characterized through the study of CTL exhaustion. These include programmed death-1 (PD-1) and its ligand (PD-L1), interleukin 10 (Il10), cytotoxic T lymphocyte antigen-4 (CTLA-4), T-cell membrane protein-3 (TIM-3), lymphocyte-activation gene 3 (LAG3) and tumor necrosis factor alpha-induced protein 8-like 2 (TIPE2), among others [ 3 , 6 , 8 , 11 , 12 , 13 ]. Although the role of endogenous metabolites in regulating these responses has been under-investigated for decades, recently, several metabolites with immunomodulatory properties have been found beyond the traditional oxylipins, arachidonic acid and omega-3 fatty acids [ 14 , 15 ] that are associated with immunomodulation.…”
Section: Introductionmentioning
confidence: 99%